Perceptions, behaviours and attitudes towards smoking held by the male partners of Chinese pregnant women: a qualitative study - Wei Xia; Ho Cheung William Li; Peige Song; Ka Yan Ho; Yuanhui Luo; Tingna Liang; Laurie Long Kwan Ho; Ankie Tan Cheung; Wenzhi Cai (BMC, 2021)
Abstract Background Direct associations of tobacco exposure during pregnancy with pregnancy complications and adverse birth outcomes have been proven. Previous studies suggest that expecting a child provides a valuable opportunity to promote behavioural changes, such as smoking cessation, among the male partners of pregnant women. Thorough understandings of Chinese expectant fathers' smoking behaviour during the transition to fatherhood is a prerequisite to the development of appropriate interventions to facilitate smoking cessation. This study aimed to explore the perceptions, behaviours and attitudes related to smoking among male partners of pregnant women in China. Methods A descriptive phenomenological approach was adopted. A purposive sample of expectant fathers aged 18 years or older who had a tobacco use history within the past year were recruited at obstetrics and gynaecology clinics and invited to participate in one-to-one, 20-30-min semi-structured interviews. The data analysis followed Colaizzi's descriptive phenomenological method. Results Twenty-five expectant fathers were interviewed. Four themes were generated: 1) the benefits of smoking and respondents' misperceptions of the impact of smoking and SHS and neglectful attitude of the impact of smoking, which were given as the major reasons for continuing to smoke; 2) factors contributing to smoking cessation, including concern for the potential health impact of continued smoking on the pregnant partner and baby, the role of being father, and the encouragement to quit from family members; and 3) perceived barriers to smoking cessation, including withdrawal symptoms or cigarette cravings, absence of smoking cessation support, and increasing stress. Conclusion This study provides a comprehensive understanding of the perception, behaviours, and attitudes related to smoking among Chinese expectant fathers. The findings of this study can guide healthcare professionals and policymakers in combining the distribution of educational information about the hazards of SHS for maternal and neonatal health with smoking cessation assistance for expectant fathers through policy initiatives and other types of incentives and programmes targeted to enhance smoking cessation among this population. Trial registration Prospectively registered at clinicaltrial.org ( NCT03401021 ) on 8 Jan 2018.